Efektivitas UU Cipta Kerja dalam Melindungi Hak Pekerja Penyandang Disabilitas - Firdaus, Indriana (Jurnal Fakta Hukum, 2024)
People with disabilities often experience discrimination, negative stigma, bullying and other unpleasant actions in the work environment. Such actions clearly violate their basic rights. Therefore, regulations are needed that are able to maintain these rights. Undang-Undang Cipta Kerja is one of the legal products created by the government in order to regulate and protect the rights of workers, including people with disabilities. However, the question that arises is how effective the UU Cipta Kerja is in regulating and protecting the rights of workers, especially people with disabilities. This research aims to analyze the effectiveness of the UU Cipta Kerja in protecting the rights of workers with disabilities. Normative research methods were used in this research, with a statue approach and conceptual approach. It is hoped that the research results will provide an overview of the extent to which the UU Cipta Kerja can provide effective protection for the rights of workers with disabilities. It is hoped that the implications of this research can provide input for improving regulations or better implementing policies to ensure that the rights of people with disabilities can be optimally protected in the work environment.